Polarization variable terahertz metasurface along the propagation path - Jitao Li; Jingyu Liu; Zhen Yue; Jie Li; Chenglong Zheng; Fan Yang; Hui Li; Yating Zhang; Yan Zhang; Jianquan Yao (Fundamental Research)
Conventional metasurfaces for terahertz polarization are limited to performing lateral (in the x-y plane) polarization control of the output wave. In such cases, the polarization state remains unchanged in each output plane along the propagation path. Herein, we propose a terahertz polarization metasurface that operates longitudinally (i.e., along the z-axis direction of propagation), which modifies the polarization state of each output plane throughout the propagation path. Our designed metasurface can control the phase delays of the left-handed and right-handed circularly polarized (LCP and RCP) components of the incident terahertz wave. This enables the LCP beam and RCP beam to converge to the z-axis through distinct paths, creating a Bessel beam. The proposed design achieved a linearly polarized terahertz wave including both LCP and RCP components with a precise phase difference Δφ at each point within a certain range along the z-axis. The Δφ varies as the propagation distance, resulting in a rotated linearly polarized output wave along the propagation path, while the rotation angle ranges from 0 to π. Based on the variable property of longitudinal polarization, we propose an application concept of dielectric refractive index sensing, in which an additional medium is placed in the terahertz propagation path and the unknown refractive index is determined by detecting the rotation angle of the output polarization state. Theoretically, the device might find potential applications in variable media excitation, terahertz communication, and terahertz radar ranging.